Effects of low-intensity pulsed ultrasound on recovery of physical impairments, functional performance and quality of life after total knee arthroplasty: Protocol for a quasi-experimental study - Munajar @ Munajat, Munayati; Mohd Nordin, Nor Azlin; Nor Hamdan, Mohamad Yahya; Zulkifly, Ahmad Hafiz (Wolters Kluwer Health, Inc, 2019)
The presence of significant pain and swelling during the acute stage following total knee arthroplasty (TKA) may limit the patients’ ability to cooperate in intensive physiotherapy interventions. Low-intensity pulsed ultrasound is one of the modalities that can be used for acute pain and swelling management. However, only one study investigated the effect of this modality in patients with TKA. There is limited documentation of the effects of combining low-intensity pulsed ultrasound in TKA rehabilitation in the recovery of physical impairments and how these influence the recovery of function after TKA. Therefore, this study is proposed with the aim to evaluate the effects of low-intensity pulsed ultrasound as an adjunct to conventional physiotherapy on the recovery of physical impairments, functional performance and quality of life after TKA surgery.